Zenith retreat / Norfazillah Ahmad ... [et al.] - Ahmad, Norfazillah; Mohammad Shah, Natra Shamaine; Mohd Nadzri, Alisya Sofiah; Halidan, Nor Puteri Ameliana (2024)
Zenith Retreat represents a harmonious balance of opposing sustainable energies, combining the power land firmness of stone with the warmth and suppleness of timber. The pavilion which is based on the ancient yin and yang philosophy, serves as a place of reflection and connection with nature. Its creative design effortlessly combines traditional craftsmanship and modern techniques to create a serene environment that promotes peace and recuperation. Visitors are invited to this multifunctional space to relax and unwind at the same time portray their masterpieces there. The Zenith Retreat’s symbiotic blending of materials and concepts creates a timeless retreat where people can discover balance, serenity and inner peace.